2020
DOI: 10.3390/cryst10080658
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Mapping of Heterogeneous Strain and Defects in Individual Magnetic Nanocrystals

Abstract: We map the three-dimensional strain heterogeneity within a single core-shell Ni nanoparticle using Bragg coherent diffractive imaging. We report the direct observation of both uniform displacements and strain within the crystalline core Ni region. We identify non-uniform displacements and dislocation morphologies across the core–shell interface, and within the outer shell at the nanoscale. By tracking individual dislocation lines in the outer shell region, and comparing the relative orientation between the Bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…BCDI has been applied in several fields of science and technology including the study of NPs in general, ,,,,, zeolites, , heterogeneous catalysis, ,, batteries, supercapacitors dielectrics, nanowires, , minerals, alloys and dealloying, nanorods, , proteins, thin films, ,…”
Section: Bcdi Applied To Electrochemistry and Heterogeneous Catalysismentioning
confidence: 99%
“…BCDI has been applied in several fields of science and technology including the study of NPs in general, ,,,,, zeolites, , heterogeneous catalysis, ,, batteries, supercapacitors dielectrics, nanowires, , minerals, alloys and dealloying, nanorods, , proteins, thin films, ,…”
Section: Bcdi Applied To Electrochemistry and Heterogeneous Catalysismentioning
confidence: 99%
“…This recovered phase contains information about distortions to the crystal lattice in the direction normal to the diffracting planes. BCDI has been used extensively to map Bragg electronic density, displacement, ferroelectric domains and strain within the volume of crystals with nanoscale resolution; [18][19][20][21][22][23][24][25] the best reported resolution to date is 4-9nm. 26 It has been shown that BCDI can detect signatures of defects by measuring the disruptions to the long-range order of the crystal.…”
mentioning
confidence: 99%